Coeliac disease in Caucasian and South Asian patients in the North West of England. Issue 4 (20th March 2019) - Adam, U. U.; Melgies, M.; Kadir, S.; Henriksen, L.; Lynch, D.
Abstract: Background: Coeliac disease is an autoimmune enteropathy characterised by mucosal inflammation subsequent to gluten exposure, leading to malabsorption. Treatment is strict dietary control, relying on the patient's ability to maintain lifestyle modifications. The present study aimed to compare clinical presentation and adherence to a gluten‐free diet between South Asian and Caucasian patients with coeliac disease in East Lancashire Methods: In total, 33 South Asian and 113 Caucasian adult patients diagnosed with coeliac disease under the care of the Dietetics Department at East Lancashire Hospitals NHS Trust were selected using a convenience sampling method and then allocated to the South Asian or Caucasian group. A subjective assessment of dietetic notes from follow‐up visits within 1 year of the first appointment was undertaken by two investigators who subsequently allocated the patients to one of the three categories: (i) fully‐adherent; (ii) partly‐adherent; and (iii) non‐adherent. Presenting complaint, vitamin D, vitamin B12, folate and ferritin levels were also compared. Results: There was a significant difference in adherence to gluten‐free diet between the groups, with a larger proportion of Caucasian patients being fully adherent to gluten‐free diet compared to South Asian patients (64.6% versus 12.1%, P  <   0.001). In addition, a significantly higher proportion of South Asian patients were vitamin D deficient compared with Caucasian patients (70.8% versus 32.8%, P  =   0.002). Conclusions: The rates of strict adherence to gluten‐free diet and vitamin D levels were significantly lower in South Asian patients with coeliac disease compared to the Caucasian coeliac population. Further studies are required to investigate the causes and improve adherence in the South Asian population.